Medial prefrontal cortical control of reward‐ and aversion‐based behavioral output: Bottom‐up modulation - Pastor, Verónica; Medina, Jorge Horacio (The European journal of neuroscience, 2021)
How does the brain guide our actions? This is a complex issue, where the medial prefrontal cortex (mPFC) plays a crucial role. The mPFC is essential for cognitive flexibility and decision making. These functions are related to reward‐ and aversion‐based learning, which ultimately drive behavior. Though, cortical projections and modulatory systems that may regulate those processes in the mPFC are less understood. How does the mPFC regulate approach‐avoidance behavior in the case of conflicting aversive and appetitive stimuli? This is likely dependent on the bottom‐up neuromodulation of the mPFC projection neurons. In this review, we integrate behavioral‐, pharmacological‐, and viral‐based circuit manipulation data showing the involvement of mPFC dopaminergic, noradrenergic, cholinergic, and serotoninergic inputs in reward and aversion processing. Given that an incorrect balance of reward and aversion value could be a key problem in mental diseases such as substance use disorders, we discuss outstanding questions for future research on the role of mPFC modulation in reward and aversion. Medial prefrontal cortex (mPFC) is involved in reward‐ and aversion‐based behavior. Modern techniques shed light on the role of mPFC projections to specific output targets in approach and avoidance behavioral output. However, how the mPFC change from pursuing reward to avoid punishment remains unknown. Modulatory systems are key for tuning the mPFC control of reward‐ and aversion‐based behavior, and their impairment may induce neuropsychiatric diseases such as substance use disorder.